2017
DOI: 10.1186/s12955-017-0663-3
|View full text |Cite
|
Sign up to set email alerts
|

Oral impacts on quality of life and problem-oriented attendance among South East London adults

Abstract: BackgroundDental care seeking behaviour is often driven by symptoms. The value of oral health related quality of life (OHRQoL) measures to predict utilisation of dental services is unknown. This study aims to explore the association between OHRQoL and problem-oriented dental attendance among adults.MethodsWe analysed cross-sectional data for 705 adults, aged 16 years and above, living in three boroughs of Inner South East London. Data were collected during structured interviews at home. The short form of the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
3
7
1
4
Order By: Relevance
“…In accordance with previous research (25,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42), we observed socio-economic inequalities in the SROH and OHRQoL of the adults in our sample, and also corroborating previous research, these inequalities were associated with the socio-economic characteristics, a problem-oriented approach to utilization of dental services (35,(42)(43)(44)(45)(46)(47)(48), and self-reported general health (7,10,(49)(50)(51). Socio-economic disparities can affect psychosocial factors, such as optimism, coping styles, and personal control related to health outcomes, which can be predictive of SROH and OHRQoL (38,41,52).…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with previous research (25,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42), we observed socio-economic inequalities in the SROH and OHRQoL of the adults in our sample, and also corroborating previous research, these inequalities were associated with the socio-economic characteristics, a problem-oriented approach to utilization of dental services (35,(42)(43)(44)(45)(46)(47)(48), and self-reported general health (7,10,(49)(50)(51). Socio-economic disparities can affect psychosocial factors, such as optimism, coping styles, and personal control related to health outcomes, which can be predictive of SROH and OHRQoL (38,41,52).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies from the UK (Gaewkhiew et al 2017) and Australia (Brennan et al 2019) have indicated that poor OHRQoL was higher among those who recently visited the dentist, which was also found in this study. The reason for this association seems to be counterintuitive as one might think that those who do not visit a dentist regularly might experience more oral disease and, consequently, a poorer OHRQoL compared with those who do visit a dentist (Montero et al 2011).…”
Section: Discussionsupporting
confidence: 87%
“…The context of the associations between poor OHRQoL and dental visits has to be considered: The percentage of those visiting a dentist was lower than what has been found elsewhere (CDA 2017), which might have explained the higher prevalence of oral diseases and risk factors in this population (Bhat et al 2015; Bhat et al 2018) and yet dental visits do not occur as frequently as reported by other populations. Also, the reporting of oral health impacts was lower compared with other studies (Gaewkhiew et al 2017; Brennan et al 2019), which might be due to the fact that rural Indian people may be more concerned about their daily functioning and not psychosocial status being affected by poor oral health, and the fact that they consider losing teeth as a natural process of aging (Singh et al 2013). It might also be due to the fact that some individuals become accustomed to accepting less than ideal health status as normal.…”
Section: Discussionmentioning
confidence: 71%
“…Previous research has indicated that participants with poorer OHRQoL were more likely to have recently visited the dentist . Inconsistent with these results, we did not observe this association in the present study.…”
Section: Discussioncontrasting
confidence: 64%